2021
DOI: 10.1007/s11606-021-07134-4
|View full text |Cite
|
Sign up to set email alerts
|

Women, Younger Clinicians’, and Caregivers’ Experiences of Burnout and Well-being During COVID-19 in a US Healthcare System

Abstract: Background The COVID-19 pandemic brought rapid changes to the work and personal lives of clinicians. Objective To assess clinician burnout and well-being during the COVID-19 pandemic and guide healthcare system improvement efforts. Design A survey asking about clinician burnout, well-being, and work experiences. Participants Surveys distributed to 8141 clinicians from June to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 41 publications
(54 reference statements)
2
34
0
Order By: Relevance
“…More women than men reported that childcare/caregiving affected work during the COVID-19 pandemic (32.9% vs. 19.0%, P < 0.01). 19 Persistent posttraumatic stress or burnout symptoms were not associated with demographic data. Nevertheless, our sample is small to perform a more comprehensive analysis, including additional factors associated with persistent psychological difficulties.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…More women than men reported that childcare/caregiving affected work during the COVID-19 pandemic (32.9% vs. 19.0%, P < 0.01). 19 Persistent posttraumatic stress or burnout symptoms were not associated with demographic data. Nevertheless, our sample is small to perform a more comprehensive analysis, including additional factors associated with persistent psychological difficulties.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the COVID-19 pandemic affected remote learning for children, which probably mainly affected the mothers, especially during the COVID-19 lockdown when school and nurseries were closed. For example, Dillon et al 19 showed that burnout was more common among women than among men (39.0% vs. 22.7%, P < 0.01) in 3176 U.S. physicians. More women than men reported that childcare/caregiving affected work during the COVID-19 pandemic (32.9% vs. 19.0%, P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Since the SMB reflects the degree of emotional exhaustion and is free and easy to administer, it has become widely used as an alternative to the MBI. 8 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Since the SMB reflects the degree of emotional exhaustion and is free and easy to administer, it has become widely used as an alternative to the MBI. 8,15,16 In Japan, there are few studies on burnout, and only one nationwide survey on medical resident burnout has been published. 17 However, if the SMB were available and shown to accurately assess burnout, it would facilitate research on burnout and its assessment in medical institutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation